Diarising climate change: Johannesburg youth's outlook on their future - Mouton, Schalk (My University, 2019)
While the youth has been named as one of the most important target audiences to communicate the challenges and future implications of climate change, very little has been done globally to engage with them on the issue and include them in the conversation on how to mitigate against, and adapt to climate change. The youth of South Africa faces a highly uncertain future, with various challenges such as high levels of inequality and unemployment as well as an uncertain political and economic future. With such pressing, immediate challenges, it is doubtful that an issue such as climate change – which for most societies is a very distant challenge, both in time and space – would be an issue that South Africa’s youth would be concerned with. Communication practices for climate change have largely been ineffective to spark a change in behaviour amongst most communities. Yet, it is in the youth that we find both a challenge and an opportunity to overcome this ‘wicked’ problem. If we can engage the youth, we can help to empower them as change agents in their households, their communities and, in future, in their workplaces. In order to do this, however, we need to gain their trust, and encourage them to become partners in the challenge against climate change. In order to do this, it is crucial to understand the values, beliefs and norms that they hold dear. It is also important to understand who influences them the most, and who they would trust to engage with respect to climate change. This qualitative study is an attempt to understand what some of the youth at the University of the Witwatersrand in Johannesburg, South Africa, think and believe about climate change; how their behaviour towards climate change is shaped; who are the people that they trust, and who would influence them the most. It also is an attempt to gain an understanding of how this knowledge could be used effectively, empowering the youth to become the agents of change that we need to overcome one of the biggest challenges of our – and more importantly – their live